Organizational Considerations in the Evaluation of Capital Assets: Toward a Resource-Based View of Strategic Investment by Firms - Robins, James A. (Organization Science, 1992)
During the last three decades, sophisticated techniques for analysis of market investment have been developed by financial economists. At the same time, however, concepts and methods for analysis of resource allocation within firms have lagged behind market theory. The analysis of investment within firms has been based primarily on applications of economic theory that exhibit serious weaknesses. The special problems associated with analysis of investment in firms have become an important concern of strategic management. Recent “resource-based” approaches to strategy have developed valuable insights into the limitations of economic analysis of the firm. Although the resource-based work has not yet provided formal methods comparable to the Capital Asset Pricing Model, it has made important progress in building foundations for an alternative analysis of economic organization. This paper explores weaknesses in the financial economic analysis of the firm and examines alternative perspectives in the work on resource-based strategy. The paper focuses on problems associated with use of market models such as the CAPM for capital allocation within firms. Working from basic premises of transaction-cost economics, the paper identifies important flaws in financial-economic techniques for defining hurdle rates for capital projects. The paper discusses underlying logical problems associated with the application of market theory to complex organizations and examines ways that alternative approaches to resource allocation have begun to evolve within the field of strategic management.